Feasibility of percutaneous coronary intervention before mitral NeoChord implantation: Single‐center early results. Issue 11 (30th August 2021) - Pradegan, Nicola; D'Onofrio, Augusto; Longinotti, Lorenzo; Evangelista, Giuseppe; Mastro, Florinda; Fiocco, Alessandro; Nadali, Matteo; Gerosa, Gino
Abstract: Background and Aim of the study: Micro‐invasive cardiac surgery identifies procedures performed off‐pump, on beating heart. Aim of this single‐center retrospective study was to assess early outcomes of a totally micro‐invasive strategy (percutaneous coronary intervention—PCI—followed by transapical off‐pump NeoChord mitral repair) in patients with concomitant coronary artery disease (CAD) and degenerative mitral regurgitation (MR). Methods: We analyzed early and 1‐year follow‐up data of patients who underwent a NeoChord procedure between November 2013 and May 2020, and preceded by PCI. Outcomes were defined according to Mitral Valve Academic Research Consortium (MVARC) definitions. Results: Among 220 patients who underwent NeoChord repair in the study period, 17 (7.7%) underwent PCI previously. CAD was an accidental finding during preoperative mitral evaluation in nine patients (52.9%; Group 1; with PCI occurring 2 months before NeoChord, interquartile range [IQR] = 1.0–2.7), while it was part of the past medical history in the remaining eight patients (47.1%; Group 2; with PCI occurring 30 months before NeoChord, IQR = 24.5–64.0). Twelve patients (70.6%) presented single‐vessel disease, two patients (11.8%) triple‐vessel disease. No surgical revisions for bleeding were required after NeoChord. At 1‐year follow‐up ( n = 16), all patients were alive and did not experience major adverse events except for one reoperation due to late NeoChord failure. None required additional PCI. Conclusion: In our experience, PCI before NeoChord seems safe and effective, and performing PCI before NeoChord might not affect outcomes. A totally micro‐invasive strategy in selected patients suffering from MR and CAD should be considered as a reasonable alternative to conventional surgery.